2021
DOI: 10.1002/alz.12371
|View full text |Cite
|
Sign up to set email alerts
|

The BIN1 rs744373 Alzheimer's disease risk SNP is associated with faster Aβ‐associated tau accumulation and cognitive decline

Abstract: Introduction The BIN1 rs744373 single nucleotide polymorphism (SNP) is a key genetic risk locus for Alzheimer's disease (AD) associated with tau pathology. Because tau typically accumulates in response to amyloid beta (Aβ), we tested whether BIN1 rs744373 accelerates Aβ‐related tau accumulation. Methods We included two samples (Alzheimer's Disease Neuroimaging Initiative [ADNI], n = 153; Biomarkers for Identifying Neurodegenerative Disorders Early and Reliably [BioFINDER], n = 63) with longitudinal 18F‐Flortau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Even if our current study was not intended to directly assess functional consequences of AD risk-related BIN1 polymorphisms but to focus on BIN1 isoforms function in neurons, which are still insufficiently described and understood, it may provide a context for BIN1-associated risk, namely the dysregulation of early endosome size and function. Up to now and not exclusive from each other, BIN1 polymorphisms have been associated with Tau but not amyloid loads in post-mortem AD brain tissue [ 9 ] and they are consistently associated with faster Aβ-associated Tau-PET accumulation and cognitive decline in AD patient [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if our current study was not intended to directly assess functional consequences of AD risk-related BIN1 polymorphisms but to focus on BIN1 isoforms function in neurons, which are still insufficiently described and understood, it may provide a context for BIN1-associated risk, namely the dysregulation of early endosome size and function. Up to now and not exclusive from each other, BIN1 polymorphisms have been associated with Tau but not amyloid loads in post-mortem AD brain tissue [ 9 ] and they are consistently associated with faster Aβ-associated Tau-PET accumulation and cognitive decline in AD patient [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therriault et al [ 86 ] and Neitzel et al [ 89 ] independently evaluated different datasets and reported that APOE ε4 is associated with higher tau accumulation and that this association is independent of amyloid burden. Regarding other AD candidate genes, Franzmeier et al [ 87 , 90 ] and Neitzel et al [ 91 ] suggested that the BIN1 rs744373 SNP and Klotho-VS heterozygosity are associated with higher and lower pathologic tau levels, respectively, by analyses of variance and multiple linear regression.…”
Section: Implementation Of Ad Imaging Biomarker Genomics Studiesmentioning
confidence: 99%
“…The use of prior knowledge, such as the Allen Human Brain atlas (AHBA), can facilitate calculations in brain imaging biomarker genomics and correlate spatial variations at the molecular scale with macroscopic neuroimaging phenotypes. For example, Franzmeier et al [ 90 ] and Neitzel et al [ 91 ] have used the AHBA to explore associations of BIN1 rs744373 and KL-VS heterozygosity with tau accumulation, respectively. Moreover, Sepulcre et al [ 172 ] have developed a novel graph theory approach named directional graph theory regression (DGTR) to investigate the intersection of tau/Aβ pathological changes in the brain and the genetic transcriptome of AHBA.…”
Section: Key Considerations and Perspectives Regarding Ad Imaging Bio...mentioning
confidence: 99%
“…in ADNI CNs. 9 Based on the power analysis, a sample of 59 individuals per group would be required to reach a power of 80% at α = 0.05 to replicate the reported BIN1 rs744373 effect on global tau burden (effect size = 0.26). Similarly, one would need to include 48 individuals per group to reach a power of 80% at α = 0.05 for detecting a BIN1 rs744373 effect on global tau burden (effect size = 0.29) in BioFINDER CNs.…”
Section: Statistical Analysesmentioning
confidence: 99%
“… 8 According to a follow‐up paper, BIN1 risk‐allele carriers show accelerated tau‐PET accumulation at higher Aβ levels. 9 …”
Section: Introductionmentioning
confidence: 99%